JRA-55AMIP: The Japanese 55-year Reanalysis AMIP-type Simulation ... - Japan Meteorological Agency/Japan (UCAR/NCAR - Research Data Archive, 2015)
As a subset of the Japanese 55-year Reanalysis (JRA-55) project, an experiment using the global atmospheric model of the JRA-55 was conducted by the Meteorological Research Institute of the Japan Meteorological Agency. The experiment, named the JRA-55AMIP, has been carried out by prescribing the same boundary conditions and radiative forcing of JRA-55, including the historical observed sea surface temperature, sea ice concentration, greenhouse gases, etc., with no use of atmospheric observational data. This project is intended to assess systematic errors of the model. ...